Exploring the Determinants of Polypharmacy Prescribing and Dispensing Behaviours in Primary Care for the Elderly—Protocol for a Qualitative Study - Taghy, Najwa (Int J Environ Res Public Health, 2021)
Polypharmacy is becoming increasingly common, especially among the elderly. It often has a negative connotation, but is sometimes necessary or even desirable, and needed to categorize polypharmacy as appropriate or inappropriate. The challenge is in ensuring that this is considered appropriate when necessary. We aimed to develop an evidence-based intervention to reduce the risks associated with using a systematic approach, involving key stakeholders in prescribing and dispensing drugs to the elderly in primary care. The purpose of this study is to identify the key components which are perceived as influencing these behaviours. It is a qualitative study of general practitioners (GPS) and community pharmacists involved in the care of the elderly. The main inclusion criterion is the geographic location. Qualitative data will be generated from one-on-one, semi-structured interviews and processed for thematic content analysis. Our approach integrates the patient pathway in primary care. It considers the fact that GP and pharmacist behaviours are far from being independent. This study represents the first step in the process of developing an intervention theory which involves a crossover between data from the literature and the knowledge of experts, allowing us to interrogate hypotheses about the influences and mechanisms associated with prescribing and dispensing drugs to the elderly in primary care.